2008
DOI: 10.1093/jn/138.3.630
|View full text |Cite
|
Sign up to set email alerts
|

A Results Framework Serves Both Program Design and Delivery Science

Abstract: Health programmers and researchers must collaborate despite different mandates and technical languages. A results framework is a simple model that both disciplines can use to understand complexity, clarify assumptions and hypotheses, design programs, and ask questions to inform action research. Typically, a health program's results framework has 3 tiers and 6 boxes: a base of 4 health service intermediate results (access, quality, demand, and environment), which lead to a midlevel strategic objective (use of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The study in Peru found that, although implementation of the program at health centers in Peru was “less than optimal” overall, aspects of the implementation were nevertheless significant variables in the impact pathway to contribute to success. Overall, few studies tend to look systematically at delivery‐related factors, although they are recognized as being important to the adoption of practices and impact in nutrition programs …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study in Peru found that, although implementation of the program at health centers in Peru was “less than optimal” overall, aspects of the implementation were nevertheless significant variables in the impact pathway to contribute to success. Overall, few studies tend to look systematically at delivery‐related factors, although they are recognized as being important to the adoption of practices and impact in nutrition programs …”
Section: Methodsmentioning
confidence: 99%
“…Results frameworks: These are one of the most common tools used in development to guide the design, monitoring, and evaluation of policies and programs, and their applicability in nutrition programs has been described by Marsh. 30 They help rationalize and make explicit the relations among inputs and the anticipated outputs, outcomes, and impacts, but they do not by themselves contain or reveal the underlying biological, behavioral, or social theory by which inputs are expected to produce the desired results. 2.…”
Section: Box 1 Expandability Of the Nutrition Implementation Framewomentioning
confidence: 99%
See 1 more Smart Citation
“…These include impact and process evaluations of large-scale programs and in demonstration or feasibility trials (154,215,216); formative or operations research to understand or address specific implementation issues or bottlenecks (217,218); retrospective "lessons learned" exercises (219-221); the development and application of tools to strengthen program design and/or implementation, such as log frames, program impact pathways, and program assessment methodologies (222)(223)(224); a large number of descriptive accounts of efforts to implement interventions, programs, or policies at organizational, local, and/or national levels (225)(226)(227)(228)(229)(230); and the development of new evaluation approaches sensitive to the needs and realities of implementation (35,231). This work often is driven by the needs of program implementers (and some funders) to strengthen the extent and quality of implementation and often involves collaboration between researchers and implementers.…”
Section: Guiding Framework Principles and Approachesmentioning
confidence: 99%
“…9 In Stockholm (May 2009), ccm.org proposed a generic evaluation framework for iCCM (Figure 1). 9 On the basis of a results framework,10 the schema includes outcomes (boxes in top three rows) and processes (partitioned box at the bottom) to implement the strategy.…”
mentioning
confidence: 99%